1987
DOI: 10.2170/jjphysiol.37.497
|View full text |Cite
|
Sign up to set email alerts
|

Non-neural electrical responses of smooth muscle cells of the rabbit basilar artery to electrical field stimulation.

Abstract: In smooth muscle cells of the rabbit basilar artery, field stimulation evoked a depolarizing response which consisted of a fast (1-3 s duration) and a following slow (1-4min duration) component. The amplitude of these responses increased in an intensity-dependent manner and, when exceeding 10-15 mV, a spike potential was generated. During generation of the slow depolarization, ionic conductances of the membrane were increased. When outward current pulses with long duration (2-3 s) were applied to the smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…In the basilar artery, multiple substances may be released during activation of endothelial cells, not only EDRF and EDHF but also endotheliumderived contracting factor (De Mey & Vanhoutte, 1983;Nagao & Suzuki, 1987) and also relaxing substances, such as prostacyclin (PGI2) (Moncada et al, 1977;Baenziger et al, 1977;Eldor et al, 1981;Domae & Kuriyama, 1986). It is unlikely that the effects of ACh on the guinea-pig basilar artery can be accounted for by the release of PGI2 since the relaxant response to ACh is unchanged by indomethacin and PGI2 does not hyperpolarize the membrane (unpublished observations).…”
Section: Discussionmentioning
confidence: 98%
“…In the basilar artery, multiple substances may be released during activation of endothelial cells, not only EDRF and EDHF but also endotheliumderived contracting factor (De Mey & Vanhoutte, 1983;Nagao & Suzuki, 1987) and also relaxing substances, such as prostacyclin (PGI2) (Moncada et al, 1977;Baenziger et al, 1977;Eldor et al, 1981;Domae & Kuriyama, 1986). It is unlikely that the effects of ACh on the guinea-pig basilar artery can be accounted for by the release of PGI2 since the relaxant response to ACh is unchanged by indomethacin and PGI2 does not hyperpolarize the membrane (unpublished observations).…”
Section: Discussionmentioning
confidence: 98%
“…As there are gap junctions between endothelial and adjacent smooth muscle cells (Rhodin, 1967;Taugner, Kirchheim & Forssmann, 1984), electrical coupling between these two types of cells may occur . In fact, the non-neuronal depolarizing responses elicited by electrical field stimulation in smooth muscle cells of the rabbit basilar artery are not generated after removal of the endothelium (Nagao & Suzuki, 1987). However, evidence that the hyperpolarization of smooth muscle cells in tissues with no endothelium can be produced indirectly (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the mechanically agitated bronchioles, almost all the examined sections (95%) had lost 60-90% of the epithelial luminal surface. We also used hypo-osmolarity shock to destroy the epithelial layer, as is done for endothelial cells in blood vessels (Bolton, Lang & Takewaki, 1984;Nagao & Suzuki, 1987). Histological examination of the bronchioles revealed that the epithelial luminal surface was completely destroyed after the hypo-osmolarity shock, as has been noted in blood vessels (Nagao & Suzuki, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…The fixed needle was also used for electrical stimulation of ring preparations of the bronchiole. As required for the study, the epithelial cells were removed mechanically by rubbing the internal surface of the bronchioles with a fine silver wire (200 ,Im diameter) or by hypo-osmolarity shock by exposing the inner lumen of the bronchioles to distilled water for about 30-60 s as has previously been done in vascular tissues for removal of endothelial cells (Bolton et al 1984;Nagao & Suzuki, 1987).…”
Section: Methodsmentioning
confidence: 99%